Competitive Strategy with Swot Analysis to Increase Sales at Mentai Rice Business - Astriyani, Rini (Siber International Journal of Digital Business (SIJDB), 2023)
One strategy that is very effective in improving the ability to compete is to use SWOT analysis, companies can develop more effective strategies to improve their ability to compete. The object of this research is Mentai rice Buma which is a business unit located in pekayon jaya, south Bekasi. The purpose of writing this article is to find out internal factors and external factors and create an effective business strategy to compete again in the future. The type of research conducted in this study uses descriptive qualitative research using SWOT analysis and data collection through observation and interviews with consumers of Mentai Rice Buma in Bekasi. A competitive strategy is a business plan that shows business knowledge about how to compete against competitors with the same goal of winning the competition. Swot analysis is an analysis method to show various factors regarding the strengths and weaknesses of the organization as well as opportunities and threats from the environment. Sales is the process of finding and engaging customers so that they can match their needs with the products offered. Based on the results of the SWOT analysis, it can be concluded that the competitive strengths possessed compared to its competitors based on the SWOT Matrix, are Having a unique taste image to attract new customers, Providing a menu of mentai rice with raw materials with high quality.